FORMULATION AND DEVELOPMENT OF LIP BALM FROM RED SEAWEED (GELIDIUM SP.) EXTRACT AS A NATURAL ANTIOXIDANT (Proceedings OPTIMAL, 2025)
This study aimed to formulate and evaluate lip balm preparations incorporating red seaweed (Gelidium sp.) extract as a natural active ingredient with antioxidant and moisturizing potential. Four formulations were prepared: F0 (without extract), FI (5% extract), FII (7.5% extract), and FIII (10% extract). The formulations were evaluated through organoleptic observation, homogeneity testing, pH measurement, melting point determination, spreadability testing, qualitative antioxidant testing using DPPH, and a consumer preference test. The organoleptic evaluation showed a consistent strawberry aroma across all formulations, with color and texture differences becoming more pronounced as extract concentration increased. Homogeneity testing indicated that F0 and FI met quality standards, while FII and FIII did not, likely due to uneven pigment distribution caused by the extract. All formulations exhibited pH values within the physiological lip pH range (4.0–6.5) and melting points between 51–58 °C, aligning with the acceptable cosmetic range (50–70 °C). All samples also met the required spreadability standard (5–7 cm). Qualitative DPPH testing revealed positive antioxidant activity for FI, FII, and FIII, with stronger activity observed at higher extract concentrations. A preference test with 30 panelists showed that F0 and FI were most preferred for color and texture, while FII and FIII were less favored despite similar aroma and moisturizing characteristics. These results indicate that red seaweed (Gelidium sp.) extract can be effectively utilized as an active ingredient in lip balm formulations, particularly at lower concentrations, to provide antioxidant benefits and maintain desirable physical and sensory characteristics.